Herpes Simplex Conjunctivitis and Recurrent Chalazia in a Patient DOCK8 Deficiency. (17th November 2022) - Le, Tinh; Can, Basak; Orge, Faruk
ABSTRACT: Purpose: To report a case of recurrent chalazia and Herpes Simplex conjunctivitis in a patient with DOCK8 deficiency. Case Report: We report the case of a 15-year-old male patient with genetically diagnosed DOCK8 deficiency who presented with a left lower eyelid mass and left eye conjunctivitis. The lesion did not resolve despite aggressive measures, including topical steroids, topical antibiotics, and multiple debulking procedures but eventually resolved after the initiation of intravenous acyclovir. The diagnosis of HSV infection was supported by pathology findings from the eyelid mass. Conclusion: Patients with DOCK8 deficiency can present with a variety of cutaneous viral infections. In our case, a DOCK8-deficient patient with chalazia and conjunctivitis resistant to antibiotics, steroids and debulking responded to intravenous acyclovir.